PENGEMBANGAN BOOKLET TIPE-TIPE STOMATA TUMBUHAN FAMILI ARACEAE DI LINGKUNGAN FKIP UNIVERSITAS LAMBUNG MANGKURAT - Helmah, Ayu Noor; Amintarti, Sri; Ajizah, Aulia (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The development of a booklet on stomatal types in the Plant Anatomy course aims to provide a supplementary teaching material. This study seeks to describe the stomatal types found in Araceae plants within the FKIP ULM Banjarmasin environment, as well as to evaluate the content relevance, feasibility, readability, and development outcomes of the booklet. This research is a type of research and development (R&D) following the 4D model, limited to the Develop stage. The subjects involved in the development and evaluation of the booklet included two lecturers from the Biology Education Study Program and nine students who had completed the Plant Anatomy course at FKIP ULM Banjarmasin. The study identified two types of stomata among nine species of Araceae plants: (1) the cyclocytic type, found in Philodendron tuxla, Dieffenbachia seguine, Spathiphyllum floribundum, Philodendron burle marx, Syngonium auritum, Alocasia sarian, and Alocasia sanderiana; and (2) the anomocytic (ranunculaceous) type, found in Caladium tricolor and Colocasia esculenta L. The booklet achieved an average score of 4.37 in the relevance test (very relevant), 4.28 in the feasibility test (very feasible), and 4.49 in the readability test (very good), indicating that the booklet is technically suitable for use as a teaching material to support the Plant Anatomy course.